2014
DOI: 10.1007/s11270-014-1922-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Enhancers and Inhibitors on Photocatalytic Sunlight Treatment of Methylene Blue

Abstract: In view of the fatal illnesses which Methylene Blue (MB) leads to upon ingestion, the present study focused on the use of natural sunlight in heterogeneous photocatalysis to decolourize MB. Most past studies utilized UV, visible or simulated sunlight in photocatalysis of MB. The present study also investigated the effects of enhancers (hydrogen peroxide and persulphate ion) and inhibitors (chloride and carbonate ions) on photodecolourization of MB. Pseudo-firstorder rate constants for each studied effect were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(22 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…Several recent researches have reported that kinetics of the photocatalytic degradation of aqueous pollutants by TiO 2 follows the Langmuir-Hinshelwood (L-H) kinetic model (Lazar et al 2012;Daghrir and Drogui 2013;Subramonian and Wu 2014). The kinetic model data were evaluated by regression analysis method using Excel software.…”
Section: Resultsmentioning
confidence: 99%
“…Several recent researches have reported that kinetics of the photocatalytic degradation of aqueous pollutants by TiO 2 follows the Langmuir-Hinshelwood (L-H) kinetic model (Lazar et al 2012;Daghrir and Drogui 2013;Subramonian and Wu 2014). The kinetic model data were evaluated by regression analysis method using Excel software.…”
Section: Resultsmentioning
confidence: 99%
“…Synthetic dyes are generally very stable to light, temperature, and microbial attack, making them recalcitrant (Pagga and Brown, 1986;Subramonian and Wu, 2014). Furthermore, dye wastewater has a large amount of suspended solids, a broadly fluctuating pH, and is highly colored (Subramonian and Wu, 2014;Wu et al, 2013). However, during last decades researchers focussed on for an effective treatment technology of dyes waste water, but no satisfactory solution has been searched for broad spectrum of dyes degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Fourier-transform infrared (FTIR) Spectrometry of No metals@PAM and FeCo@PAM was investigated. In Figure 1, the spectra of both (a) No metals@PAM and (b) FeCo@PAM exhibited many common bands, as both contained typical PAM bands, [26,27] see Figure 1. A broad band in the region 3,000-3,700 cm −1 appears in both the IR spectra, due to the OH stretching vibrations of absorbed water, the hydroxyl group being H-bound as the peak is very broad.…”
Section: Characterizationmentioning
confidence: 99%